Evaporation kinetics of nano water droplets using coarse-grained molecular dynamic simulations - Kieu, Hieu Trung (2021)
The utilization of nanocompounds can significantly enhance the production efficiency for solar steam generation, and much research and development efforts have been dedicated to designing their surface and structure to optimize the solar-heat conversion as well as evaporation performance. In particular, computational modeling studies using molecular dynamic (MD) simulations had been extensively performed for this objective. However, those studies typically assumed constant vacuum evaporation, thus yielding unrealistically high evaporation fluxes compared to laboratory and field measurements reported in the literature. To address this issue, we capture the transient thermodynamic properties of a nano water droplet that undergoes evaporation in a vapor medium under a closed periodic system with vapor pressures, using non-equilibrium MD simulations with the ELBA coarse-grain model. The changes of the nanodroplet and the localized vapor pressures inside the system from vacuum to saturation are monitored quantitatively. In addition, the varying radial extent of the Knudsen layer around the droplet is determined spatially through the transient pressure and energy distribution. The results illustrate the dynamical changes in the evaporation behavior from the diffusive-dominant to the kinetically limited transport mechanism. They also explain why the Kelvin equation can still apply in nanometer-scale systems, due to the fact that the density profiles are independent of the changes in pressure gradients. The Hertz-Knudsen Schrage equation, which is commonly used to compute the evaporation flux in the literature, is found unable to accurately predict the transient evaporative behavior observed. Thus, the results from this study illustrate that future molecular dynamic evaporation studies need to identify the location of the Knudsen layer in the simulations when calculating bulk evaporation fluxes in realistic vapor ambient conditions, due to its predominance in nanoscale interfacial processes.